Digital Innovation in Corporations: Deriving a Practical Framework for the Measurement of Success of Digital Innovation Units - Marcel Schemmel (Junior Management Science (JUMS), 2022)
Confronted with entirely new challenges resulting from digital technologies, established corporations increasingly set up dedicated digital innovation units (DIUs) to foster digital innovation and to explore opportunities for the digital future. Although DIUs recently face criticism with regards to their performance and impact on the core organization, literature lacks in suitable approaches to assess the success of DIUs. Therefore, we derive a practical framework for the measurement of success of DIUs in the course of this research project. We develop this framework by identifying critical success factors (CSFs) and key performance indicators (KPIs). Subsequently, we merge our results with existing literature. To determine these CSFs and KPIs, we designed an explorative, qualitative-empirical case study research approach. The research design is based on a mixed-method approach that combines semi-structured interviews as core component with a supplementary survey. Conducting nine cross-industry case studies, we identified 16 CSFs and 38 objective related KPIs. Thus, the framework derived in this thesis contributes to practice and literature by addressing the existing gap in DIU and performance measurement research.
Keywords: 650; Digital innovation units; performance measurement; critical success factors; key performance indicators; qualitative case studies